HUMANITARIAN OF THINGS IN THE NOVEL OF ”ATRA” BY DEYAR EREDING - ISMAIL HAJI, NAFEESA (Journal of Duhok University, 2019)
one of them. His novel 'Atra' is one the works that has been written in a new and attractive style.  The interesting thing in the novel is that most of the characters, if not all, are animals, plants and things, all of them speak, think and In recent years, a number of young writers have appeared in Iraqi Kurdistan,  Deyar Erediny is express their feelings, as Erediny gives them the features of human being, and that is what I mean by ‘humanization’. In Erediny’s  world, everything is innocent, good and human, except for man himself. Although, narrating stories on the tongue of animals or making characters of things is not something new in literature, but in the novel "Atra" this has taken a wide space and, most importantly all things are human except human himself. And this is what made us believe that the subject deserves study and was the motivation to write this research. This study is an attempt to identify the reasons behind Erediny's style and this phenomenon in his novel. The hypothesis of this work is that there is a connection between the writer's thought and the social class that he belongs, and his novel. This study aims to prove that as same as the reification which was the result of the capitalist system, giving everything the features of human except human himself in Atra is a result of ugliness, bloody and terrorist actions of human being and crimes that he committed by the name of religion. All this could be a result of capitalism too. This study seeks to analyze the novel and to reach the results based on the critical views that are looking at the relationship between the literary text and the society, especially Lucian Goldman's theory of ‘structural structuralism’